Hypovitaminosis D Is Prevalent in Patients With Renal AL Amyloidosis and Associated With Renal Outcome - Muchtar, Eli; Drake, Matthew T.; Leung, Nelson; Dispenzieri, Angela; Lacy, Martha Q.; Buadi, Francis K.; Dingli, David; Hayman, Suzanne R.; Kapoor, Prashant; Hwa, Yi Lisa; Fonder, Amie; Hobbs, Miriam; et al. (Frontiers in Endocrinology, 2022)
Introduction Vitamin D deficiency is common, but no data have been reported on vitamin D levels in light chain (AL) amyloidosis. Patients and Methods In this exploratory study, stored serum samples from 173 patients with newly diagnosed AL amyloidosis were analyzed for vitamin studies which included 25-hydroxyvitamin D [25(OH)D], 1,25-dihydroxyvitamin D [1,25(OH)2D] and vitamin D binding protein (DBP). Measurements were made by liquid chromatography-tandem mass spectrometry. Kidney survival and overall survival (OS) were assessed in association to vitamin D status. Results Cardiac and kidney involvement occurred in 69% and 63% of patients, respectively. 25(OH)D deficiency (<20 ng/mL) was seen in 56.6% of the patients and was notably found among patients with heavy proteinuria (96%), hypoalbuminemia (84.3%) and morbidly obese patients (68.3%). Heavy proteinuria (>5 gr/24-h) and vitamin D supplementation were independent predictors of 25(OH)D level on nominal multivariate regression analysis. 1,25(0H)2D deficiency was noted in 37.6% of patients and was independently associated with low eGFR and hypoalbuminemia. Progression to ESRD occurred in 23.7% of evaluable patients. Patients who progressed to ESRD had lower serum 25(OH)D and 1,25(OH)2D levels compared to those who did not progress to ESRD. On a multivariate analysis, severe 25(OH)D deficiency was an independent predictor of progression to ESRD as was renal stage, while 1,25(OH)2D deficiency was not. Conclusions Hypovitaminosis D is common in AL amyloidosis, particularly among patients with heavy proteinuria. Severe 25(OH)D deficiency at time of diagnosis predicts progression to ESRD.